Budaya Komunitas Virtual Indonesia Book Party di Media Sosial Instagram (Studi Etnografi Virtual Komunitas @Indobookparty di Instagram) - Yuki Amalia Prasetyo Putri; Aulia Rahmawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines the culture of the Indonesia Book Party community through the @indobookparty Instagram account using Christine Hine’s virtual ethnography method. Data were collected through virtual observation, in-depth online interviews, and documentation, and analyzed using four levels: media space, media archive, media object, and experiential stories. At the media space level, Instagram is used to share activities and shape identity. Most members use their main accounts, while some use second accounts to maintain privacy, reflecting Wood & Smith’s identity theory. The account is managed to encourage open and equal interaction, in line with Gane & Beer’s interactivity theory. At the media archive level, identity is shown through visuals, emojis, and unique language. At the media object level, interaction is active through feeds, stories, and DMs, with both secondary and circular communication patterns. At the experiential stories level, the community reflects values of openness and togetherness, both online and offline, showing that online culture reflects real-life connections.